Discrimination of bile acids by the rainbow trout olfactory system: Evidence as potential pheromone - Giaquinto, Percilia [UNESP]; Hara, Toshiaki J. (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2008)
Electro-olfactogram recording was used to determine whether the olfactory epithelium of adult rainbow trout is specifically sensitive to bile acids, some of which have been hypothesized to function as pheromones. Of 38 bile acids that had been pre-screened for olfactory activity, 6 were selected. The rainbow trout-specific bile acids, taurocholic acid (TCA), and taurolithocholic: acid 3-sulfate (TLS) were the most potent compounds tested. TLS had a distinctive dose-response curve. Cross-adaptation experiments demonstrated that sensitivity to bile acids is attributable to at least 3 independent classes of olfactory receptor sites. Our data suggest that bile acids are discriminated by olfaction in rainbow trout, supporting the possibility that these compounds function as pheromones.
Keywords: Bile acids; Chemical signals; Electro-olfactogram; Olfaction; Pheromones; Rainbow trout